The Latency, Accuracy, and Battery (LAB) Abstraction: Programmer Productivity and Energy Efficiency for Continuous Mobile Context Sensing - Kansal, Aman; Saponas, Scott; Brush, A.J.; Mytkowicz, Todd; McKinley, Kathryn S (OOPSLA, 2013)
Emerging mobile applications that sense context are poised to delight and entertain us with timely news and events, health tracking, and social connections. Unfortunately, sensing algorithms quickly drain the phone's battery. Developers can overcome battery drain by carefully optimizing context sensing but that makes programming with context arduous and ties applications to current sensing hardware. These types of applications embody a twist on the classic tension between programmer productivity and performance due to their combination of requirements. This paper identifies the latency, accuracy, battery (LAB) abstraction to resolve this tension. We implement and evaluate LAB in a system called Senergy. Developers specify their LAB requirements independent of inference algorithms and sensors. Senergy delivers energy efficient context while meeting the requirements and adapts as hardware changes. We demonstrate LAB's expressiveness by using it to implement 22 context sensing algorithms for four types of context (location, driving, walking, and stationary) and six diverse applications. To demonstrate LAB’s energy optimizations, we show often an order of magnitude improvements in energy efficiency on applications compared to prior approaches. This relatively simple, priority based API, may serve as a blueprint for future API design in an increasingly complex design space that must tradeoff latency, accuracy, and efficiency to meet application needs and attain portability across evolving, sensor-rich, heterogeneous, and power constrained hardware.